Water and sanitation problems in urban local authorities in Zimbabwe: the case study of Epworth local Board - Nyaruwabvu, Try (Midlands State University, 2018)
The purpose of this study was to assess water and sanitation problems in urban local authorities in Zimbabwe through giving reference to Epworth local board. The gradual decline in the provision of water and sanitation services amid the majority of local authorities in Zimbabwe has prompted the need to undertake this study. The findings of the research can therefore be useful in finding ways to improve the management and planning process of urban residential areas that respond to the issues of inadequate water supply and sanitation services. The study employed both qualitative and quantitative approach in gathering data. In dealing with the main objective of the study the research used both case study and descriptive research designs. A sample of 75 respondents that comprises of residents, council officials, councilors, NGO‟s, representative of Epworth Residents development association and development committee members were chosen to participate in this study. Systematic random sampling, purposive, convenient and snowballing sampling techniques were used in selecting participants during data collection. Primary data was collected through administration of questionnaires to the residents, site observations of water and sanitation facilities and then interviews with Key informant from council officials and other stakeholders. The study area was Epworth and this research was only confined to ward 1, 6 &7. The research established that water and sanitation services in Epworth are below optimum level. The study findings revealed that a number of challenges are being faced by the local board in the provision of water and sanitation services. These include low revenue base, population growth, illegal settlements, water source, vandalism, resource constrains and among others. These challenges were proven to be a stumbling block in the efficient provision of water and sanitation services. As a result, this situation negatively affects the lives of residents in Epworth as there are left exposed to water borne diseases, unstable livelihoods and interruption of economic activities. In response to the same a number of coping strategies has been adopted by members of this community to increase quantity of water, improve quality and accommodate shortages. The study concludes that the performance of the local authority in relation to the provision of water and sanitation services is not being up to the required standard. In the last chapter, the study concludes by giving recommendation based on the research findings. The recommendations include engaging the private sector to source resources, investment in more temporary water infrastructure, central government support in terms of capital projects, increased stakeholder participation in the development process and engagement of NGOs in provision of water and sanitation services.